The Leeds Evaluation of Efficacy of Detoxification Study (LEEDS) prisons project: a randomised controlled trial comparing dihydrocodeine and buprenorphine for opiate detoxification - Li Ryan; Adams Clive E; El-Sayeh Hany G; Wright Nat MJ; Sheard Laura; Tompkins Charlotte NE (BMC, 2009)
Abstract Background Many opiate users entering British prisons require prescribed medication to help them achieve abstinence. This commonly takes the form of a detoxification regime. Previously, a range of detoxification agents have been prescribed without a clear evidence base to recommend a drug of choice. There are few trials and very few in the prison setting. This study compares dihydrocodeine with buprenorphine. Methods Open label, pragmatic, randomised controlled trial in a large remand prison in the North of England. Ninety adult male prisoners requesting an opiate detoxification were randomised to receive either daily sublingual buprenorphine or daily oral dihydrocodeine, given in the context of routine care. All participants gave written, informed consent. Reducing regimens were within a standard regimen of not more than 20 days and were at the discretion of the prescribing doctor. Primary outcome was abstinence from illicit opiates as indicated by a urine test at five days post detoxification. Secondary outcomes were collected during the detoxification period and then at one, three and six months post detoxification. Analysis was undertaken using relative risk tests for categorical data and unpaired t-tests for continuous data. Results 64% of those approached took part in the study. 63 men (70%) gave a urine sample at five days post detoxification. At the completion of detoxification, by intention to treat analysis, a higher proportion of people allocated to buprenorphine provided a urine sample negative for opiates (abstinent) compared with those who received dihydrocodeine (57% vs 35%, RR 1.61 CI 1.02-2.56). At the 1, 3 and 6 month follow-up points, there were no significant differences for urine samples negative for opiates between the two groups. Follow up rates were low for those participants who had subsequently been released into the community. Conclusion These findings would suggest that dihydrocodeine should not be routinely used for detoxification from opiates in the prison setting. The high relapse rate amongst those achieving abstinence would suggest the need for an increased emphasis upon opiate maintenance programmes in the prison setting. Trial registration Current Controlled Trials ISRCTN07752728